The Gender Earnings Gap in Britain - Karen Mumford; Peter N. Smith (Institute for the Study of Labor (IZA), 2004)
The earnings gap between male and female employees is substantial and persistent. Using new data for Britain, this paper shows that an important contribution to this gap is made by the workplace in which the employee works. Evidence for workplace and occupational segregation as partial explanations of the earnings gap is presented. Having allowed also for individual worker characteristics there remains a substantial within-workplace and withinoccupation gender earnings gap. The contribution of these factors, as well as the earnings gap itself, differ significantly across sectors of the labour market. The relative unimportance of occupational segregation and the large remaining gender earnings gap suggest that stronger enforcement of Equal Pay legislation is likely to be the most appropriate policy response.
Keywords: J7; J3; 330; gender earnings; wage-gap; fixed-effects; segregation; Lohndifferenzierung; Geschlechterdiskriminierung; Arbeitsplatz; Arbeitsmarktsegmentierung; Schätzung; Grossbritannien